Discovering entrepreneurship competencies through problem‐based learning in higher education students - Sousa, M. (2022)
The increase in student engagement in the learning process has driven educators to use more dynamic pedagogical methodologies. Several studies have shown evidence of increased interest in learning when real‐world problems are integrated into the learning environment. This paper presents the competencies developed by higher education students through application of the problem‐based learning (PBL) methodology in higher education courses. The research begins with the identification of a set of competencies developed by higher education students in other studies developed and reported in the last five years and includes them in a survey to analyze the level of development of those competencies when problem‐based learning is applied in university courses. To identify the competencies developed by applying the problem‐based learning methodology, theresearch employed a document analysis and a survey of the students that participated in the experimental application. The research questions “What are the competencies developed by students in problem‐based learning?” and “Are the competencies identified by the students sufficiently learned in universities?” guided the study. The competencies found by the students were identified through a questionnaire given as an online survey to 76 students. The key outcome of the research is the identification in the bachelor courses of the competencies perceived as essential by students participating in the application of PBL in terms of their advancement.